The 18th International Conference on Experimental Mechanics 2018
DOI: 10.3390/icem18-05224
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Procedure for Bond, Anchorage and Strain-Hardening Behavior of Textile-Reinforced Cementitious Composites

Abstract: A fast adoption of innovative composite materials such as textile reinforced concrete (TRC) in practice is hindered by the lack of efficient and standardized characterization and design procedures. In this paper, we discuss results of uniaxial tensile tests and double sided pullout tests. The analysis of the tests is done with a modelling framework for tensile behavior developed at IMB RWTH Aachen. The overall goal is to simulate the tensile response of composite specimen based on the reinforcement and matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…of TRM through experimental analysis. However, only a few studies have analyzed the bonding behavior of coated carbon textile in concrete and the flexural behavior of coated carbon-textile-reinforced cementitious materials [23,24]. In addition, although the research results [11] have suggested that TRM can improve performance under serviceability loads by increasing the flexural and shear capacity compared to existing RC members, the field application of TRM as a structural member necessitates a concise and reliable analysis model to predict the structural behavior of TRM.…”
Section: Introductionmentioning
confidence: 99%
“…of TRM through experimental analysis. However, only a few studies have analyzed the bonding behavior of coated carbon textile in concrete and the flexural behavior of coated carbon-textile-reinforced cementitious materials [23,24]. In addition, although the research results [11] have suggested that TRM can improve performance under serviceability loads by increasing the flexural and shear capacity compared to existing RC members, the field application of TRM as a structural member necessitates a concise and reliable analysis model to predict the structural behavior of TRM.…”
Section: Introductionmentioning
confidence: 99%